Numerical simulation method of ultrasonic wave propagation in gas-liquid two-phase flow of deepwater riser. (1st March 2019) - Xu, Yuqiang; Guan, Zhichuan; Xu, Chuanbin; Liu, Yongwang; Tian, Yang; Sheng, Yanan; Sun, Shuo
Highlights: Numerical simulation method of ultrasonic propagation in flow of risers was set up. Time domain diagram of received signals was analyzed. Cross-correlation function was used to quantitatively analyze the received signals. The method can be used as an effective supplement to the experiment. Abstract: The ultrasonic transmission monitoring in risers is a promising method for the early detection of gas kick in deepwater drilling. It is difficult to obtain satisfactory results using only theoretical calculation because the ultrasonic wave propagation in the multiphase flow in risers is very complicated. In addition, the key parameters such as bubble shape and void fraction of two-phase flow are hard to be accurately controlled and measured. In view of the above-mentioned facts, this paper aims to analyze the principle and physical model of ultrasonic monitoring of gas kick in risers, and to establish a numerical simulation model based on COMSOL platform. Through an analysis of the numerical simulation results, it was found that the time domain diagram of the received signals contains longitudinal wave, transverse wave, surface wave and coda wave. The cross-correlation function was used to quantitatively analyze the waveform of the received signals under different void fraction conditions. It also suggested that the direct wave was insensitive to the void fraction while the coda wave was sensitive to the void fraction, which was verified through frequency domain analysis. By establishing the experimental system, the attenuation coefficient was used to verify the numerical simulation results. After comparing and analyzing data, this paper argued that the numerical simulation method established in the project can be used as an effective supplement to experiments, and it can be used to calculate and analyze the ultrasonic propagation and attenuation under conditions, such as different bubble sizes and densities, and bubble non-uniform distribution, which can not be accurately and quantitatively measured or controlled in the experiments.